Differential muscle-type expression of the Drosophila troponin T gene. A 3-base pair microexon is involved in visceral and adult hypodermic muscle specification. - Benoist, P.; Mas, J.A.; Marco, R.; Cervera, M. (Journal of Biological Chemistry, 1998)
The complete genomic organization of the Drosophila troponin T (TnT) gene shows many interesting features, including the presence of a microexon of only 3 nucleotides conserved among Drosophilidae. It is the smallest bona fide exon so far described, placing a new lower limit on the nucleotide number required for correct splicing. Four muscle-type specific transcripts are generated by developmentally regulated alternative splicing. Exons 3, 4, and 5 are absent in the transcript present in jump and flight muscles. A total of 11 exons are present in the adult hypodermic muscles transcript, whereas the microexon is absent in the larval hypodermic musculature. The two isoforms differ in a lysine residue. Post-translational regulation of the flight muscles/tergal depressor of the trochanter-specific isoform is involved in flight and/or jump function. The interaction domains of TnT in the tropomyosin-troponin complex are strongly conserved in the known vertebrate and invertebrate TnT sequences, whereas the terminal regions show an important variability. The COOH-terminal region shows important phylogenetic variations, whereas the NH2-terminal domain is associated with specific muscle types in a particular organism, a finding that discloses a selective value for these domains in the functionality of distinct muscles in different organisms.